An overview on niosomes as efficient drug carriers - RIZWANA KHAN; RAGHUVEER IRCHHAIYA (International Journal of Pharma and Bio Sciences, 2017)
Over the past years the treatments of disease have undergone a revolutionary change. With the advancement of pharmaceutical science not only novel drug delivery system have been developed but also emphasis has been laid to deliver the active constituent to the diseased site.The basic component of such a system is a suitable carrier that protects the active medicament from degradation or clearance from the body.Niosomes are one such vesicular drug delivery system which are composed of non-ionic surfactant vesicles formed by self-association of hydrated surfactant. Being biodegradable, non-toxic, stable and inexpensive, these are becoming increasingly popular in cosmetic and in pharma industry.Various reports have shown promising future of niosomes by oral, ocular,parentral and transdermal route.The first report on surfactant vesicles came from the cosmetic applications devised by L’Oreal.Since then, there has been increasing interest in the use of niosomes in the pharmaceutical, cosmetic, and food industries.This article reviews the current widening interest of noisomes in medicine.The present review compiles the types of niosomes,their basic structure.It also attemps to provide exhaustive collection of recent research on niosomal preprations with special emphasis on strategies used to enhance the delivery of drugs via oral,occular and transdermal route with their reported preclinical and clinical studies illustrating enhanced safety and efficacy.